2007
DOI: 10.1200/jco.2007.11.8554
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy in Malignant Glioma: Standard of Care and Future Directions

Abstract: Glioma has been considered resistant to chemotherapy and radiation. Recently, concomitant and adjuvant chemoradiotherapy with temozolomide has become the standard treatment for newly diagnosed glioblastoma. Conversely (neo-)adjuvant PCV (procarbazine, lomustine, vincristine) failed to improve survival in the more chemoresponsive tumor entities of anaplastic oligoastrocytoma and oligodendroglioma. Preclinical investigations suggest synergism or additivity of radiotherapy and temozolomide in glioma cell lines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
326
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 474 publications
(332 citation statements)
references
References 85 publications
2
326
0
4
Order By: Relevance
“…1 Once diagnosed, the overall prognosis for patients remains poor, and their clinical course is complicated and unpredictable because of significant morbidity from both tumor-related neurologic and cognitive symptoms as well as treatment-related toxicity. 2 Uncertainty, defined as an individual's lack of ability to determine the meaning of illness-related events, 3 may pervade the whole illness trajectory of PBTs. One of our studies demonstrated that patients' uncertainty during active treatment was as high as in the newly diagnosed period.…”
Section: Introductionmentioning
confidence: 99%
“…1 Once diagnosed, the overall prognosis for patients remains poor, and their clinical course is complicated and unpredictable because of significant morbidity from both tumor-related neurologic and cognitive symptoms as well as treatment-related toxicity. 2 Uncertainty, defined as an individual's lack of ability to determine the meaning of illness-related events, 3 may pervade the whole illness trajectory of PBTs. One of our studies demonstrated that patients' uncertainty during active treatment was as high as in the newly diagnosed period.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery followed by chemotherapy is the normal treatment regimen for gliomas, most malignant gliomas are resistant to chemotherapeutic agents. Because the blood-brain barrier (BBB) restricts and regulates the delivery of chemotherapy agents, the prognosis for glioma is poor (Stupp et al, 2007;Villano et al, 2009). Therefore, it is necessary to develop highly permeable agents that cross the BBB for the chemotherapeutic treatment of patients with malignant glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant gliomas are a group of primary brain tumors that have remained resistant to therapy and that have a dismal prognosis (Buckner et al, 2007;Stupp et al, 2007). Part of the reason for this state of affairs is that although gliomas rarely metastasize outside the CNS, they are capable of spreading long distances within the brain (Sherer, 1940;Burger and Kleihues, 1989;Hoelzinger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%